2021
DOI: 10.3389/fspor.2021.635103
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Training Load, Match Activities, and Health Problems in Norwegian Youth Elite Handball Players Over One Competitive Season

Abstract: Talent development is integral to the policy and organizational practice of competitive sport, but has also been associated with excessive amounts of training and competition, and athlete injuries and illnesses. The lack of available prospective data on the training and match activities of youth athletes and their health problems is therefore of concern. The aim of this study was two-fold: (a) to examine the amount and frequency of training load, match activities, injury and illness incidence, and prevalence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
3
15
1
Order By: Relevance
“…We observed a slightly higher weekly illness prevalence in female youth floorball players than males (13% vs 11%), and our findings concur with the results from several different sports in Norwegian youth elite athletes 8 18. In elite adult sports as well, female athletes appear to be more prone to illness,9 yet the influence of sex on illness prevalence remains unclear in elite youth sports 10–13.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed a slightly higher weekly illness prevalence in female youth floorball players than males (13% vs 11%), and our findings concur with the results from several different sports in Norwegian youth elite athletes 8 18. In elite adult sports as well, female athletes appear to be more prone to illness,9 yet the influence of sex on illness prevalence remains unclear in elite youth sports 10–13.…”
Section: Discussionsupporting
confidence: 88%
“…The average weekly illness prevalence was 12%, which is comparable to Norwegian youth elite athletes participating in technical sports (10%),8 but higher than for Norwegian elite youth athletes participating in team sports (8%–9%),8 18 Dutch junior tennis players (6%),10 and Irish elite youth track and field athletes (7%) 19. The Swedish floorball season runs from September to March (autumn and winter months) when illness is more prevalent compared with summer months when athletics and tennis are played.…”
Section: Discussionmentioning
confidence: 84%
“…Comparable studies with the OSTRC-O or OSTRC-H have shown a higher response rate among adult athletes [ 10 14 ]. A higher response rate was also found in studies with younger athletes [ 1 , 2 , 6 , 16 18 , 24 , 25 ]. Some of these studies, however, relied heavily on parental engagement [ 1 , 18 ], weekly follow ups and methods to collect data retrospectively (e.g., interviews; weekly follow-ups) [ 2 , 6 , 18 ].…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, a range of elite sport organizations have employed the tools in their sport injury research and clinical health monitoring programmes [ 15 ]. In recent years, the two questionnaires have also been applied to children and adolescents of different sport contexts [ 1 , 2 , 6 , 7 , 16 18 ]. Most of these studies, however, applied the questionnaires without reporting any consideration regarding methodological suitability and implications for application.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained training load and injury data collected from three cohorts: Norwegian elite U-19 football players (n=81, 55% male, mean age: 17 years, SD: 1 year), 12 one male football team from the Norwegian Premier League (n=36, mean age: 26 years (SD: 4)) 13 and elite youth handball players recruited from Norwegian sports high schools (n=205, 36% male, mean age: 17 years (SD: 1)). 14 These cohorts were followed for 104, 323 and 237 days, respectively, during the competitive season.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%